RAMBU SOLO AND BUFFALO AT TANA TORAJA OF SOUTH SULAWESI - Saleh, Ikrar Mohammad; Sirajuddin, Sitti Nurani; Aminawar, Muhammad (Proceeding Buffalo International Conference, 2013)
Toraja traditional feast "Rambu Solo-Rambu Tuka" and Buffalo can not be released in the lifestyle of the Toraja people, like the two sides of the one coin. Both of these parties, especially "Rambu Solo", buffalo sacrifice was excessive in 2 (two) decades. Symptoms of unhealthy competition among the family/clan,  led to uncontrollable slaugthering of buffalo. The Rambu Solo feast of Nek Sarring from December 2011 to January 2012 spent more than 200 buffaloes, approximately 350 buffaloes according to the participants . This situation is exacerbated by the promotion of  Tanah Toraja as a tourist destination which has contributed to the slaughtering (massacre) of excessive buffaloes. As a tourist destination, the appeal of the "Rambu Solo" is extraordinary, due to the unique and attractiveness, uncomparable with any other parts of the world. The aims of this study are to determine how many buffaloes should be sacrificed at every party?  This is to remind the family or clan to fulfill their religious obligations and sacrifice proportional number of buffaloes in religious and cultural viewpoints of Torajans. This is a qualitative research of which the primary and secondary data were collected through focus group discussions from April to June, 2013, and then analyzed descriptively. The results of the research indicaed that participants who represent the Torajans have not considered that one day, in the near future, the buffalo will be scarce, making it difficult to conduct  the "Rambu Solo and Rambu Tuka".  However, participants believed that the demand for buffalo tends to increase from day to day.  Buffalo as a vehicle to heaven "Fuya" will be demanded continuously as a basis of Torajans traditional attributes. UNESCO has declared Toraja as a world heritage.